Penganggaran Program Pengembangan Kompetensi Pegawai PT Kereta Commuter Indonesia (KAI Commuter) - Chandra Wijaya; Utami, Sawitri Budi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was motivated by indications of problems in the budgeting process for the employee competency development program at PT Kereta Commuter Indonesia (KAI Commuter), it was the discrepancy between the budget that had been determined in the Company's Work Plan and Budget (RKAP) and its realization. In 2019, there was a realization of an employee competency development program that exceeded the budget set out in PT Kereta Commuter Indonesia's 2019. This research aims to describe the budgeting process for the PT Kereta Commuter Indonesia (KAI Commuter) employee competency development program by analyzing the budgeting stage procedures: preparation stage, forming stage, ratification (validation) stage, as well as implementation and accountability stages. The research method used was descriptive research with a qualitative approach. The data collection techniques used in this research was interview, documentation and observation methods. Based on the research results, researchers can conclude that PT Kereta Commuter Indonesia prepares budgets using a mixed approach method between a bottom up approach and a top down approach. Keywords: Budgeting, Budget, Employee Competency Development, RKAP, Budgeting Stage